PENGAWASAN KESELAMATAN OPERASI OLEH SEKSI PENGOPERASIAN OTORITAS BANDAR UDARA WILAYAH III DI BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Rifqo Desy Ghanimah (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Operation is very important for flight safety so that if there are obstacles that arise can be quickly resolved, such as when there are height violations in the Flight Operation Safety Area, especially in the Inner Horizontal Area of Juanda International Airport due to the construction of telecommunications towers. The purpose of this research is to find out the process of supervising safety operations at Juanda International Airport and to find out the follow-up of the Region III Airport Authority if it finds obstacles to safety operations at Juanda International Airport. Using a qualitative approach method, the research was conducted. Techniques for gathering data include interviews, observation, and documenting of relevant parties. The three steps of data analysis employed are data reduction, data presentation, and conclusion. Supervision of the safety of flight operations at Juanda International Airport by the Surabaya Region III Airport Authority Office, has been running well with the last time there was an indication of obstacles in 2006, namely the construction of a telecommunications tower with a height of 45 meters in the Inner Horizontal Subsurface Area which does not have a complete license and the height of the tower exceeds the specified limit. By conducting flight operation safety area socialization at least once a year, the Region III Airport Authority, Airport Operator, and local government have created effective communication with the community around Juanda International Airport Surabaya.